Análise da viabilidade de concentrar potássio de siltitos verdes por flotação em célula - Cordeiro, Laryssa Christina Batista (2018)
Potassium is a macronutrient essential for agriculture, as it acts in plants in metabolic and enzymatic activities directly linked to its growth. Brazil has a significant dependence on potassium imports to supply more than 90% of the domestic consumption. The internal production is limited to one single mine currently in operation, the Taquari Vassouras Mine, located in the state of Sergipe and explored by the Vale Fertilizers company. Since agribusiness is a pillar of Brazil economy, the country faces deficit in its domestic production of fertilizers as a limiter for increasing agricultural productivity. In this context, the search for new alternatives and potential sources of potassium has significantly increased. The silicate rock “Verdete”, found in the surroundings of Cedro do Abaeté city (MG), in the region of Alto Paranaiba, is a potential source of potassium. It is a large reserve with average grades of 10% K2O and near the country's largest agricultural region, the “Cerrado”. The present work aims to characterize and process the “Verdete” rock, evaluating the flotation process as a possible method of ore separation and concentration. Samples of “Verdete” were characterized by Granulometric analysis, X-Ray Fluorescence (XRF) and X-Ray Diffraction (XRD). It has been proven that the “Verdete” rock is enriched in potassium (above 11%) and composed of quartz, micas and potassium feldspars. Flotation tests were carried out with freshly extracted rocks, and with rocks calcined with MgCl2 and CaCl2.2H2O, in bench scale flotation cells. The product of each test was analyzed by XRF and XRD. The results showed no significant separation in flotation tests carried out with freshly extracted rocks, different from the tests performed with calcined rocks, where some elements were concentrated. The flotation products of testes carried out with rocks calcined with MgCl2 showed high concentration of Mg in the flotation fraction, especially in the test conducted using oleic acid as collector. For tests performed with rocks calcined with CaCl2.2H2O, some elements were concentrated, but the results were considered irrelevant due to the low recovery efficiency.